Passive Clutch System for the Selection of Concentric and Eccentric Exercises - Jisu Jeong; Wonseok Shin; Yuri Song; Yoonjin Kim; Suncheol Kwon; Youngjin Na (IEEE Access)
Bidirectional exercises that involve repeated concentric and eccentric contractions can be performed using simple tools such as pull-up bands or dumbbells. However, injuries can occur if one cannot overcome the excessive resistance relative to physical capabilities, particularly during eccentric contractions. Based on the pawl–ratchet clutch mechanism and an elastic band, we developed a portable exercise device that allows performing unidirectional or bidirectional exercises involving concentric/eccentric contractions, or both. The device has a clutch mode and a resistance mode, and it allows the user to choose between concentric and eccentric contractions by selecting the mode. The feasibility and effectiveness of the device in the flexion–extension movements of the human elbow were evaluated, and electromyography signals were measured. The results showed that, from the moment the clutch is released, the electromyography signal of the agonist muscle decreased significantly to a magnitude similar to that observed during free movement, confirming that the device allows the user to concentrate on concentric movements. We also found that the exercise resistance increased with increasing applied spring stiffness. Our versatile device has the potential to enable effective movements not only for intensive unidirectional exercises but also for the rehabilitation of subjects at risk of injury.